Menstrual hygiene patterns and practices among rural adolescent school girls - Chinta, Kumar; P., Sasikala; V., Chandrasekhar; C., Jayanth; A., Geethanjali (International Journal Of Community Medicine And Public Health, 2018)
Background: Menstruation is described as the periodic vaginal bleeding that occurs with the shedding of the uterine mucosa. Issues associated with menstruation are never discussed openly and the silence surrounding menstruation burdens young girls by keeping them ignorant of this biological function. The taboo surrounding menstruation in society prevents girls from articulating their needs and problems of poor menstrual hygiene management have been ignored or misunderstood. Implications of ignoring this issue of menstruation are serious and at times life threatening. Methods: This study is a cross-sectional observational study conducted among 217 adolescent girls studying in government high schools located in the field practice area of rural health training centre attached to the department of community medicine, Narayana Medical College, Nellore. Results: Out of 169 girls who have attained menarche, 154 (91.12%) were having periods at regular intervals. Among 154 girls with regular menstrual cycle majority (55.2%) had 28-31 day cycle. Out of 169 girls who had attained menarche at the time of study 76.9% reported that they use sanitary napkins for absorption of blood during menstruation. The most common method of disposal of material used for absorption of blood during menstruation was burning (91.7%) and 65.7% were using soap for washing private parts. Conclusions: The study concludes that majority of adolescent girls had regular menstrual cycles and majority of the respondents were using sanitary napkins.